Effectiveness Of Glut Palmitate Salt As Coupling Agent Compared To Polyethylene Grafted Maleic Anhydride And 3- Aminopropyltrimethoxy Silane In High Density Polyethylene And Natural Rubber Composite - Samsudin, Dalina (2018)
Coupling agents play an important role in polymers composite where they can enhance the interactions between matrix polymers and fillers. Thus, the growth in the coupling agents' research is in line with the growth of production of new polymers composite. Therefore, in this research, a coupling agent called Glut Palmitate salt (GP), that can be used to enhance matrix and filler interfaces in silica-filled high-density polyethylene composite (PE/S), kenaf bast fibre filled high density polyethylene composites (PE/KB), silica-filled natural rubber composite (NR/S) and kenaf bast fibre filled natural rubber composites (NR/KB) has been produced. GP was synthesized from palmitic acid and L-glutamine by acid-alkali titration method. To investigate the effectiveness of this GP as a coupling agent in a high-density polyethylene composite (PE) system, the GP was incorporated into composites with different contents (0.5, 1, 2 and 3 phr). The effectiveness of GP was compared to polyethylene maleic anhydride (PE-g-MAH) on polyethylene composites by processing torque, mechanical and thermal properties, water absorption, morphology and interaction of matrix-filler interfaces. In the presence of the GP and the PE-g-MAH in PE/S composite, the tensile strength, modulus, degree of crystallinity and thermal stability were increased as compared to control composites. Meanwhile, for the PE/KB composite, it showed an increament in tensile strength, modulus, degree of crystallinity and thermal stability when the GP and the PE-g-MAH are added. In both PE/S and PE/KB composites, the addition of GP at 1 phr resulted in higher tensile strength, impact strength, and degree of crystallinity than the PE-g-MAH at same composition. A study to test the GP efficiency on different matrices that is natural rubber was also performed, where the GP contents (1, 3, 5, 7, 9, and 11 phr) have been incorporated into silica-filled natural rubber composites (NR/S). The scorch time, maximum torque, crosslink density, tensile strength, modulus, hardness and thermal stability shows the optimum value when 9 phr GP was added. Meanwhile, cure time, minimum torque and rubber-filler interaction decreased with the addition of 9 phr GP. For kenaf bast fibre-filled natural rubber composites (NR/KB) system, the tested GP content is 1, 3, 5, and 7 phr. There was an increament in maximum torque, crosslink density, tensile strength, modulus, hardness and thermal stability with the addition of 3 phr GP in the composite. Addition of GP in NR/S composite resulted in higher tensile strength, elongation at break composites and thermal stability compared with Aminepropyl trimethoxy silane (APMS). Meanwhile in NR/KB, the APMS showed higher tensile strength, and thermal stability with good rubber filler interaction compared with GP as a coupling agent. The effectiveness of coupling agents was proven by Scanning Electron Microscopy (SEM), where the micrograph of tensile failure surface for all composite incorporated with GP, PE-g-MAH and APMS coupling agents showed promote better adhesion between matrix and filler as compared to composites without incorporation of the coupling agent. This is supported by Fourier Transform Infra-Red Spectroscopy (FTIR) study which the absorption peak associate with formation of hydrogen bonding, van der Walls interaction and ester and amide bonds were recorded in the IR spectra when the coupling agents were added in the composites.